DAMPAK PANDEMI COVID-19 TERHADAP SEKTOR PARIWISATA DI KOTA BANDA ACEH - arief putra pratama (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2023)
The government issued a policy of social restrictions until the closure of tourist objects in Banda Aceh City as an effort to overcome Covid-19. This policy has an impact on business actors in the tourism sector, because many events that should be held in 2020 must be canceled so that the activities of actors in the tourism sector must stop and even suffer losses. This study aims to determine the impact of the Covid-19 pandemic on the tourism sector in Banda Aceh City and the Banda Aceh City Government's policies towards business actors in the tourism sector. This study uses a qualitative method with a descriptive approach and uses public policy theory and the concept of tourism development as an analytical tool. The results of this study indicate that the impact of Covid-19 in Banda Aceh City includes negative impacts and positive impacts. The Banda Aceh City Government's efforts towards business actors in the tourism sector are more of a derivative policy from the Ministry of Tourism and Creative Economy.traders souvenir. This study concludes that the negative impacts are in the form of losses, business closures, to the loss of livelihoods and incomes for people who live from the tourism sector. The positive impact is in the form of learning in critical times, as an opportunity for tourism development to as an opportunity to increase tourism. The Banda Aceh City Government also does not prioritize the impacts experienced by actors in the tourism sector, as seen from the lack of policies that are shown directly to business actors in the tourism sector. This study suggests that the Banda Aceh City Government evaluate policies related to the pandemic condition so that the object of the policy is more focused than the parties who should not be the object of the policy.